Model Penentuan Jumlah Produksi yang Optimal pada Rantai Pasok dengan Produsen Tunggal dan Multi-Retailer - Prayoga Rizky Hermawan; Said Salim Dahda; Deny Andesta (Universitas Teuku Umar, 2021)
Determining the optimal size of procurement or production is the key word in determining optimal inventory. An integrated procurement and production size optimization model becomes a model that provides optimal results for all parties involved in the supply chain. This study proposes the development of a single producer and multi retailer supply chain model with the aim of minimizing the total inventory cost (TIC). The company distributes products to each retailer for further sale to consumers by the retailer. The annual demand from retailers is assumed to be different. Model development is carried out to obtain optimal production quantities for producers, optimal delivery quantities and determine the optimal number of retailers. The determination is based on the manufacturer's production cycle time is the same as the inventory cycle time at each retailer is the same. A simple algorithm is used to determine the optimal cycle time which can be followed by determining the optimal production size, optimal number of shipments and optimal number of retailers. At the end of this study, a numerical example of the use of a model that has been built based on case study data of a fertilizer industry is presented as a producer and its partners as retailers. The results of the numerical examples that have been carried out show that the optimal number of retailers is 3 retailers with an optimal production of 742 units, the determination of the optimal number of retailers is obtained from experiments with the lowest TIC value.